Analisis Keterkaitan Antar Sektor dalam Perekonomian Wilayah Jawa Barat - Benny Rachman (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 1993)
A region will change depending on its ability to produce goods and services. In an attempt to predict changes that occur in a region, the analysis in this paper emphasis the importance of direct and indirect economic impact of sectoral activities in West Java. The results of the analysis show that electricity, gas and drinking water supply sector and textile sector have important role in generating income, while the sector of services/others and the estate sector have a major role in employment generation. Trade sector and non-metals mining and food sector show the highest ranks in backward linkages. In terms of forward linkages, the sector of food/beverages, textile industri, and non-metal mining have the highest ranks.